Dinamika haji Indonesia sejak era kolonial dan problematika calon haji ilegal - Moh. Rosyid (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2017)
The number of Indonesian pilgrims every year is increasing. On the other hand, the allocation of the number of pilgrims to be dispatched is limited by the quota. This triggers the waiting list and the share of various hajj efforts despite the violation of the law. However, not pilgrims know that pilgrimage using other country’s passport is a violation of Law No. 12 of 2006 on Citizenship and possible losing of one's nationality. From historical perspective, Muslims’ pilgrim dated back from the 16th century. At that time, there was strong suspicion that upon returning from pilgrimage, Muslims tend to be “rebellious” and initiated movement against the Dutch colonial government. Thus, the Dutch made a strict regulation concerning the Hajj and scrutinized Muslims before pilgrimage, while staying in Mecca and after their return. Among the movement against the Dutch led by Muslim upon returning the Hajj was the Padri movement. Nowadays, the number of Muslims who intend to go Hajj is rising significantly, and the waiting list goes for 15 to 20 years. The long list caused some people to find a way to go for Hajj including manipulation of citizenship documents, such as using passport of other countries. In respond to this situation, the government tries to negotiate with the Saudi government to increase the Hajj quota for Indonesians. Another effort is borrowing the remaining quota of neighboring countries. There is also suggestion to close the Hajj registration for some time and the need to revise the Hajj Law.